Site preference of metallic elements in M23C6 carbide in a Ni-based single crystal superalloy. (5th September 2017) - Xiang, Sisi; Mao, Shengcheng; Shen, Zhenju; Long, Haibo; Wei, Hua; Ma, Shiyu; Zhang, JianXin; Chen, Yanhui; Zhang, Jianfei; Zhang, Bin; Liu, Yinong
Abstract: M23 C6 carbide is a common precipitate phase present in Ni-based superalloys. The carbide is generally an alloy carbine and often contains more than one metallic element. In this study, the site preference of metallic elements in M23 C6 carbide in a Ni-based single crystal was determined by means of aberration-corrected High-Angle Annular Dark Field Scanning Transmission Electron Microscopy (HAADF-STEM) technique and quantitative STEM (QSTEM)-based image simulation method. The carbide was found to contain mostly Cr and Re, with a small amount of Mo. The HAADF-STEM and QSTEM-based simulation analyses indicate that heavy atoms prefer to substitute Cr at 8c sites. Graphical abstract: Highlights: M23 C6 carbide in Ni-based single crystal superalloy was investigated using aberration-corrected HAADF-STEM technique. The M23 C6 carbide formed after creep testing, containing mostly Cr and Re, with a small amount of Mo The HAADF-STEM and QSTEM-based simulation analyses indicate that heavy atoms prefer to substitute Cr at 8c sites in Cr23 C6 .